2020
DOI: 10.1080/09500693.2020.1745926
|View full text |Cite
|
Sign up to set email alerts
|

Secondary school students’ views of nature of science in quantum physics

Abstract: Epistemological and philosophical issues have always been relevant for the foundations of physics, but usually do not find their way into secondary physics classrooms. As an exception to this, the strangeness of quantum physics (QP) naturally evokes philosophical questions, and learners might have to change their ideas about the nature of science (NOS). In this exploratory mixedmethod study, we examined possible connections between upper secondary school students' QP content knowledge and their ideas about rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 72 publications
0
30
0
Order By: Relevance
“…For QP learning with integrated STEM education, it is anticipated to be more challenging because this newly added topic is different from classical physics and has a long unclear interpretation in history (Angelo et al, 2014). Due to the confusing QP ontology, it is challenging for teachers to transfer the knowledge (Ab Rahman & Phang, 2012;Bungum et al, 2015;Shi, 2013;Stadermann & Goedhart, 2020). Besides, teachers must master the QP fundamental concepts with some mathematical formalism before transferring them to students (Angelo et al, 2014).…”
Section: Challenges In Teaching Quantum Physics With Integrated Stem Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…For QP learning with integrated STEM education, it is anticipated to be more challenging because this newly added topic is different from classical physics and has a long unclear interpretation in history (Angelo et al, 2014). Due to the confusing QP ontology, it is challenging for teachers to transfer the knowledge (Ab Rahman & Phang, 2012;Bungum et al, 2015;Shi, 2013;Stadermann & Goedhart, 2020). Besides, teachers must master the QP fundamental concepts with some mathematical formalism before transferring them to students (Angelo et al, 2014).…”
Section: Challenges In Teaching Quantum Physics With Integrated Stem Educationmentioning
confidence: 99%
“…As seen in the wave-particle duality conception, students developed misconceptions mostly impacted by other areas of knowledge, such as common sense and classical physics (Olsen, 2002), where students' conceptual frameworks were overlapped and mixed with classical physics and quantum mechanics. For example, the Newtonian-based deterministic worldview imposes their newfound knowledge (Hadzidaki et al, 2000;Kalkanis et al, 2003;Stadermann & Goedhart, 2020).…”
Section: The Anticipated Difficulties In Quantum Physics Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies found that greater exposure to inquiry-based instruction, which is expected to promote students' scientific views, is associated with lower students' science achievement (OECD, 2016;Sjoberg, 2018;Zhao, 2017). Furthermore, Stadermann and Goedhart (2020) have found that students' achievement levels did not prohibit them to hold a scientific view; students with low ability levels were found to hold scientific views about physics concepts.…”
Section: Mixed Viewsmentioning
confidence: 99%
“…Previous studies in Norway [4,6] have shown that quantum physics and relativity are among the topics that engage physics students to a high degree, and students may find these to be more relevant than topics of everyday practical use, such as electricity or friction. Stadermann and Goedhart [7] suggest that quantum physics can have an additional role in the physics curriculum by enhancing students' understanding of nature of science (NOS).…”
Section: Introductionmentioning
confidence: 99%